MULTI-YEAR BUDGET PLANNING FOCUSED ON THE GETTING OF THE RESULTS ON CAPITAL CONSTRUCTION PROGRAMS - Kusplyak G.I. (Pressing Problems of Public Administration, 2017)
There is considered the long-term budget planning as an instrument for implementing  scal policyaimed at obtaining expected results in accordance with the state's priority goals. Characterizedand schematically depicted the interrelation of strategic, speci c and operational goals in long-termbudget planning with government at the state level, regional, and community-based management inpriority areas that are enshrined in strategies, reforms or programs. There is proposed to introducethe multi-year budget-oriented to the result, based on the capital construction budgeting programswithin medium- and long-term budgets.